2012
DOI: 10.3851/imp2443
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Comparison of Second-Line Lopinavir/ Ritonavir Monotherapy versus Tenofovir/Lamivudine/ Lopinavir/Ritonavir in Patients Failing Nnrti Regimens: The HIV Star Study

Abstract: In PI-naive patients failing NNRTI-based first-line HAART, mono-LPV/r had a significantly lower proportion of patients with HIV RNA<50 copies/ml compared to the TDF/3TC/LPV/r treatment. Thus, mono-LPV/r should not be recommended as a second-line option.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(17 citation statements)
references
References 32 publications
1
16
0
Order By: Relevance
“…29,30 In children, this strategy has been evaluated in virologically suppressed children, with promising results. 31 PI monotherapy would have several advantages such as fewer pills, fewer drug interactions, and less NRTIassociated toxicity.…”
Section: Discussionmentioning
confidence: 97%
“…29,30 In children, this strategy has been evaluated in virologically suppressed children, with promising results. 31 PI monotherapy would have several advantages such as fewer pills, fewer drug interactions, and less NRTIassociated toxicity.…”
Section: Discussionmentioning
confidence: 97%
“…WHO's preferred strategy for second-line ART, based on two NRTIs + bPI combination, when NNRTI-containing regimens are used in first line, has been validated in recent clinical trials [ 4 6 ], but evidence for the choice of combinations is deemed of low quality and is derived from settings in high-resource countries [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Guidelines issued by the WHO in 2013 [ 3 ] recommend a second-line regimen based on boosted protease inhibitors (bPIs), with two nucleoside reverse transcriptase inhibitors (NRTIs), after failure of a non-nucleoside reverse transcriptase inhibitor (NNRTI)-based first-line treatment. This strategy was recently validated in three randomized clinical trials [ 4 6 ], but data on the NRTI and bPI options are lacking. In the WHO recommendations, the possible choice of bPI is between ritonavir-boosted atazanavir (ATZ/r) and ritonavir-boosted lopinavir (LPV/r), whereas ritonavir-boosted darunavir (DRV/r), considered as an option by the WHO expert panel, is finally not recommended due to non-availability as a generic co-formulation, its high price and limited registration [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…The SECOND-LINE and EARNEST studies recently showed that second-line regimens consisting of a boosted-protease inhibitor plus 2 NRTIs/NtRTIs and boosted-protease inhibitor plus raltegravir led to favorable treatment outcomes for patients with HIV after initial NNRTI-based regimen failure [ 67 , 68 ]. In protease inhibitor-naive patients failing NNRTI-based first-line ART, mono-therapy with ritonavir-boosted lopinavir had a significantly lower proportion of patients with undetectable viral load compared to the ritonavir-boosted lopinavir plus tenofovir and lamivudine [ 69 ]. Thus, ritonavir-boosted lopinavir monotherapy is not recommended as a second-line option.…”
Section: Introductionmentioning
confidence: 99%